Microplastics Baseline Surveys at the Water Surface and in Sediments of the North-East Atlantic - Maes, Thomas; Van der Meulen, Myra D.; Devriese, Lisa I.; Leslie, Heather A.; Huvet, Arnaud; Frère, Laura; Robbens, Johan; Vethaak, A. Dick (Frontiers in Marine Science, 2017)
Microplastic contamination was determined in sediments of the Southern North Sea and floating at the sea surface of North West Europe. Floating concentrations ranged between zero and 1.5 microplastic/m3, whereas microplastic concentrations in sediments ranged between zero and 3146 particles/kg dry weight sediment. In sediments, mainly fibers and spheres were found, whereas at the sea surface fragments were dominant. At the sea surface, concentrations of microplastics are lower and more variable than in sediments, meaning that larger sample sizes and water volumes are required to find detectable concentrations. We have calculated the widths of the confidence intervals (CI) for different sample sizes, to give a first indication of the necessary sample size for a microplastic survey at the water surface. Higher concentrations of floating microplastics were found near estuaries. In sediments, estuaries and areas with a high organic carbon content were likely hotspots. Standardization of monitoring methods within marine regions is recommended to compare and assess microplastics pollution over time.